Efficacy Of Antidiabetic Medications And Insulin Regime In Glycemic Control In Pregnancy (Journal of Pharmaceutical Negative Results, 2021)
Background: Gestational diabetes mellitus (GDM) is a condition characterized by impaired glucose tolerance first recognized during pregnancy. Avoiding adverse maternal and fetal outcomes necessitates good glycemic control. In this study, we assess the effectiveness of anti-diabetic and insulin regimens in the management of GDM.Objectives:to evaluate how efficient are antidiabetics drugs as well as insulins regimes use to manage blood sugar levels when pregnant in relation to patient’s family goals such as having normal baby and information for doctors on how best to treat gestational diabetes mellitus.Study design: A cross sectional study.Place and duration of study. Department of endocrinology hmc peshwar from 05-jan 2020 to july 05-2020Methods:The study employed a cross sectional study A comprehensive search was conducted across major electronic databases to identify relevant randomized controlled trials comparing various antidiabetic medications and insulin regimes in pregnant women with gestational diabetes mellitus (GDM). Studies reporting outcomes related to glycemic control, including HbA1c levels, fasting blood glucose levels, and incidence of adverse maternal or fetal outcomes, were included. Data extraction and quality assessment were performed independently by two reviewers. Network meta-analysis was conducted to compare the efficacy of different interventions, accounting for direct and indirect evidence. Sensitivity analyses were performed to assess the robustness of the findings. Subgroup analyses were conducted based on factors such as gestational age and maternal health status. The findings were synthesized to provide insights into the relative efficacy of antidiabetic medications and insulin regimes in glycemic control during pregnancy, aiming to guide clinical decision-making and improve outcomes for women with GDM.Results:The study enrolled 200 participants aged mean age 28 years old Insulin therapy had the greatest effect on HbA1c levels (mean reduction= -1 .5%) followed by oral hypoglycemic agents (mean reduction= -1.2%) and lifestyle changes (mean reduction = -0.8%). There were similar trends in fasting blood glucose levels. Maternal and fetal outcomes such as birth weight and Apgar scores were not significantly different among the treatment groups indicating that glycemic control is vital regardless of the mode of therapy.ConclusionOur study highlights the importance of individualizing GDM treatment approaches, with an emphasis on the efficiency of insulin therapy oral hypoglycemic agents, and lifestyle modifications in glycemic control. Clinical practice needs to be strengthened through more research into long-term effects on maternal and fetal results.